KEPEMIMPINAN AGILE (AGILE LEADERSHIP) DAN PROSES PENGAMBILAN KEPUTUSAN SUATU ORGANISASI - Permata, Hesty Duhita; Nurhayati, Nunung (Department of Islamic Education Management, 2024)
Leadership is the ability of an individual or a group of people to influence and guide followers or members of organization, society or team.A leader takes an important roles in organzation. There’s a few style of leadership for being a leader . Agile leadership is one of the style of leadership that’s important for organization to face VUCA era. With their characteristic of agile leadership which is adaptive, inovative, collaborative,and flexible, will give a positive impact to organizations by their good and fast decision making, and give solution for short and long time conditions